Analysis of Administrative Registration Service Factors on Patient Satisfaction (A Case Study at Ibnu Sina Hospital Makassar) - Destia Nur Milenia; Sumeidi Kadarisman; Rukhiyat Syahidin (PSPP JOURNALS, 2026)
The purpose of this study is to analyze the influence of administrative service speed, accuracy of administrative information, as well as the attitude and friendliness of administrative staff on patient satisfaction at Ibnu Sina Hospital, Makassar. Registration administrative services represent the patient’s initial contact with the hospital; therefore, their quality plays a crucial role in shaping perceptions of service quality and patient satisfaction levels. The method used was a quantitative approach involving 100 patient respondents who utilized registration administrative services, including both outpatient and inpatient care. Data were collected via a Likert-scale questionnaire and analyzed using the Multiple Step Interval (MSI) method. Data analysis included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. All 60 items were found to be valid and reliable, with Cronbach’s Alpha values ranging from 0.88 to 0.90. The research model met classical assumptions, namely normally distributed residuals (Asymp. Sig. 0.200), no multicollinearity (VIF < 1.50), no heteroscedasticity (Sig. > 0.34), and no autocorrelation (Durbin–Watson = 1.928).The results indicate that, partially, the speed of administrative service has a significant positive effect on patient satisfaction (β = 0.287; t = 3.842; Sig. 0.000), the accuracy of administrative information has a significant positive effect and is the most dominant variable (β = 0.314; t = 4.215; Sig. 0.000), and the attitude and friendliness of administrative staff have a significant positive effect on patient satisfaction (β = 0.298; t = 3.991; Sig. 0.000). Simultaneously, the three variables significantly influence patient satisfaction (F = 59.102; Sig. 0.000) with a contribution of 71.6% (R² = 0.716). The conclusion indicates that the speed of administrative service, the accuracy of administrative information, as well as the attitude and friendliness of administrative staff fall into the good to high categories and have a significant effect, both partially and simultaneously, on patient satisfaction at Ibnu Sina Hospital in Makassar, with the accuracy of administrative information being the most dominant factor.